Listening in Detail : Performances of Cuban Music - Vazquez, Alexandra T., 1976- (Book collections on Project MUSE., 2013)
Contending that the music is not a knowable entity but a spectrum of dynamic practices that elude definition, Alexandra T. Vazquez models a new way of writing about music and the meanings assigned to it.